A família Orchidaceae em um fragmento de floresta estacional semidecidual, no município de Barroso, Minas Gerais, Brasil (Lundiana: International Journal of Biodiversity, 2004)
The present study is an account of the species of Orchidaceae occurring in the Mata do Baú, localized in the municipality of Barroso, in the Campo das Vertentes in Minas Gerais. The predominant vegetational formation in the area studied is a seazonal semidecidous forest, which is associated to areas of riverine forest and of campo-cerrado. The family Orchidaceae is represented in the area by 25 genera and 44 species. The genera with higher diversity are Epidendrum and Oncidium (5 spp.), Campylocentrum (4 spp.), and Encyclia, Habenaria and Pleurothallis (with three species each one). Keys, descriptions, illustrations, geographical distribuition and taxonomic comments to each species are provided.